Blockchain in Development, Part I : A New Mechanism of 'Trust'? - Niforos, Marina (International Finance Corporation, Washington, DC, 2018)
Blockchain is an exciting new technology that may prove to be a radical innovation - similar to technologies such as the steam engine and the Internet that triggered previous industrial revolutions - with the power to disrupt existing economic and business models. It has the potential to deliver productivity gains to multiple industries, from the financial sector to energy markets, supply chains, intellectual property management, virtual firms, the public sector, and beyond. Its ability to provide disintermediation, improve transparency, and increase auditability can significantly reduce transaction costs, introduce efficiency into existing value chains, challenge revenue models, and open new markets. And blockchain may prove particularly valuable in emerging market economies. Yet the technology is in its early stages of development and serious challenges and risks, both technical and regulatory, will need to be addressed before it achieves widespread adoption. Questions remain about blockchain’s scalability, interoperability, security, transition costs, data privacy, and governance. And business leaders and policy makers will need to think long and hard about when and under what conditions a blockchain initiative may be warranted.